Unemployment Duration, Schooling and Property Crime - Bruce Chapman
It is well known that there is no consensus with respect to the relationship between unemployment and crime. As well, there is very little research on the linkages between crime and the educational experiences of young people. In this paper we show a very strong positive relationship between criminal activity and the extent of youth male long-term unemployment. We also show that criminal activity is negatively associated high school completions, and positively associated with high school non-completion rates. The analysis suggests that labour market and education policies have the potential to significantly reduce property crime. However, increased high school participation of the targeted group only decreases crime if it results in graduation. This suggests that the effectiveness of education policy is a critical influence on crime activity, a unique finding for the literature